First Impressions - Caplan, Tom (Groupwork, 2012)
The literature on groupwork largely lacks exploration of how to effectively use initial contact with a prospective group member to set the scene for efficacious engagement in group therapy, with the groupworker and fellow group members. By considering initial contact as a starting point for therapy, groupworkers can maximise clients’ chances of engaging readily with a group to start working towards a positive outcome. This initial contact - ‘intake interview’, or ‘invitation to engage in group therapy’ - gives scope to early expressions of difficult emotions and provides group members with the tools they need to begin communication with their group and in exploring their emotions and needs effectively.